Essentialism vs. social constructionism in the study of human sexuality - DeLamater, John D.; Hyde, Janet Shibley (The Journal of Sex Research, 1998)
According to classical essentialism, there are underlying true forms or essences, there is discontinuity between different forms rather than continuous variation, and these true forms are constant over time. Modern essentialism consists of a belief that certain phenomena are natural, inevitable, and biologically determined. We consider sociobiology, evolutionary psychology, genetic research, brain research, and endocrine research as examples of essentialist approaches, focusing particularly on how these research approaches treat sexual orientation and sexual attraction. Social constructionism, in contrast, rests on the belief that reality is socially constructed and emphasizes language as an important means by which we interpret experience. We briefly review social constructionist research on sexual orientation and sexual attraction. Finally, we review examples of conjoint or interactionist research, uniting biological and social influences. We conclude that, although there may be theories and research that conjoin biological and social influences, there can be no true conjoining of essentialism and social constructionism.
Keywords: approches et analyses; comparaison; construction sociale; cours; discipline; essentialisme; histoire et politique; méthodologie; postmodernisme; premier cycle; sciences humaines; sex2283; sociologie; thématiques